O governo da infância marginalizada : discursos e práticas acerca do “menor delinquente” em Sergipe (1927-1942) - Costa, Kátia Regina Lopes (2017)
The present thesis deals with the discursive, disciplinary and educational devices about the "delinquent juvenile" of the Sergipe from 1927 to 1942 and consists of socio - historical research, based on the Foucaultian approach, with the author as the theoretical and methodological basis of the analyzes Made. It presents as basic concepts that guided the analysis: device, discourse, governance and intellectual for Michel Foucault and "minor" according to the legislation, Rizzini and Câmara. Evaristo de Moraes, Leite Neto, Carvalho Neto and as a primary source the work of Franco de Vaz and judicial processes of the Judicial Branch of the State of Sergipe. It presents as a general objective to analyze the devices in relation to the "juvenile delinquent" in Sergipe from 1927 to 1942. As specific objectives, I tried to verify how the Sergipe judiciary applied the requirements of the Mello Mattos Minors Code, especially with regard to unimputability Juvenile prisoners and the separation of adult prisoners, in the absence of an adequate institution in the State; To identify the institutions that received such minors and to investigate the disciplinary and educational processes present in them and, finally, to analyze the speeches produced by the intellectuals Sergipe Leite Neto and Carvalho Neto, present in the criminal proceedings and in their publications about the "juvenile delinquent" in the period. The promulgation of the Mello Mattos Minors Code represented the culmination of the debates that circulated in Brazilian society and the compilation of laws and decrees that had been in force since the beginning of the 1920s. In Sergipe, State law nº 855 of October 31 of 1923, ordered the construction of appropriate facilities for the admission of abandoned and delinquent children. However, the first Sergipe institution specifically aimed at welcoming that public was only inaugurated in 1942, in Nossa Senhora do Socorro / SE. There is a fifteen-year hiatus between the promulgation of the Code and the inauguration of the institution. The thesis that I defend is that the Sergipe judiciary, in view of the circularity of new knowledge and practices about the "delinquent minor" and the promulgation of the Code of Minors in 1927, adopted a discursive formation articulated to these; However, they remained with practices of referrals to criminal institutions, based on the allegation that there was no institution for the reception of minors in the State. The situation of the "delinquent juvenile" in Sergipe, from the late nineteenth century to the mid-twentieth century, did not differ from other Brazilian states. With their advances and setbacks, the discourses presented a certain homogeneity, since in order to constitute real discourses and to compose the discursive field of the "delinquent minor" object they had to meet certain criteria, such as the adoption of medical and legal knowledge. In order to highlight the problems faced by the increase in criminality, or to discuss the referrals to be given to the offenders, the Sergipe intellectuals not only circulated in the State the conceptions of minority in vogue in Europe and the United States, but also produced knowledge and Disseminated through their publications and participation in Congresses.